Effects of Financial Literacy on Money Management Behavior among the Active Workforce - Dhamala, Rajendra; Gautam, Sujan; Ghimire, Prashant; Shrestha, Sanjina (Nepalese Journal of Management and Technology, 2025)
This study examines the effects of financial literacy on money management behavior among Nepal’s active workforce, with emphasis on the roles of access to financial resources, attitude toward money, motivation and discipline, and income in shaping financial decision-making. A descriptive research design was adopted using primary data collected from 270 respondents through structured Likert-scale questionnaires. Data were analyzed using descriptive statistics, correlation, and regression techniques in SPSS to assess the relationships between financial literacy and its key determinants. The findings reveal that access to financial resources is the strongest predictor of financial literacy, followed by attitude toward money and motivation and discipline, while income demonstrates only a moderate influence. Individuals with greater access to financial tools such as mobile banking, ATMs, and digital wallets, combined with positive financial attitudes and disciplined financial behavior, exhibit higher levels of financial literacy. The results further indicate that higher income alone does not guarantee effective money management in the absence of adequate financial knowledge and skills. The study underscores the importance of expanding financial access and implementing targeted financial education initiatives to promote responsible money management practices in Nepal.